2020
DOI: 10.2298/tsci200213191j
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric study on the pyrolysis kinetic mechanism of waste biomass from fruit processing industry

Abstract: The detailed kinetic analysis of slow pyrolysis process of apricot (Prunus armeniaca L.) kernal shells has been estimated, under non-isothermal conditions, through thermogravimetric analysis (TGA) and derivative thermogravimetry (DTG). Thermal decomposition was implemented using four different heating rates (5, 10, 15 and 20 ?C min-1), with consideration of how this parameter effects on the process kinetics. The higher heating rates provoke the shift of thermo-analytical curves towards more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As indicated by other investigator [32], higher heating rates increase DTG peaks, as individual devolatilization peaks overlap as well as this caused the disappearance of the second peak as shown in Figure 4(C) at 40 °C/min.…”
Section: Thermal Analysis Of Olive-solid Residuesupporting
confidence: 63%
“…As indicated by other investigator [32], higher heating rates increase DTG peaks, as individual devolatilization peaks overlap as well as this caused the disappearance of the second peak as shown in Figure 4(C) at 40 °C/min.…”
Section: Thermal Analysis Of Olive-solid Residuesupporting
confidence: 63%
“…Despite the plethora of studies on various food waste pyrolysis , few papers can be found in the literature on peach seeds pyrolysis and mainly on pretreated peach seeds, all concerning different cultivars from Serbia and Italy [48][49][50]. Therefore, this study aims to investigate the peach seeds pyrolysis from peach trees cultivated in Greece, with the aim to provide data supporting the pyrolysis process optimization, scale-up, and integration in a biorefinery concept.…”
Section: Scope and Objectivesmentioning
confidence: 99%
“…Some studies have focus on pyrolysis kinetic comparison between model-fitting and model-free methods, finding out that model-free methods provide more reliable results [38]. Because of that, model-free methods to determine pyrolysis kinetic parameters have been widely studied, providing information regarding influence of composition in kinetic parameters [39] and identifying pyrolysis process of each biomass component [40]. In the past years, DAEM method use has increased as it can simulate each component behaviour using gaussian distributions [41], however, material decomposition using DAEM is not accurately described [42].…”
Section: Introductionmentioning
confidence: 99%